Perbedaan Hasil Belajar Kognitif IPA Antara yang Menggunakan Model Pembelajaran Discovery Learning dan model pembelajaran learning cycle 7e di kelas V Sd Negeri Cimanggu 01 - Isnawati, Pebri; Rahmayanti, Ai Ade (Jurnal Pancar, 2017)
This research aims to know the Difference of Cognitive Learning Result IPA between Using Discovery Learning Model and Learning Cycle 7E in Class V SD Negeri Cimanggu 01. The research method used is the quasi experimental. The sample is as much as 2 classes; class V A and V B as much as 52 students. The research instrument used is a test of students? learning result on the ecosystem concept. The technique of analysis the data uses t-test. The research result shows that there is no difference of cognitive IPA learning result between using discovery learning model and learning cycle 7E in class V SD Negeri Cimanggu 01. The writer suggests trying to give learning treatment by using discovery learning model and learning cycle 7E model on another lesson and also in choosing learning model, the teacher should adjust to the students? development level and the material will be given.